Grading lymph node metastasis: a feasible approach for prognostication of patients with stage III colorectal cancer. Issue 9 (16th June 2015) - Resch, Annika; Harbaum, Lars; Pollheimer, Marion J; Kornprat, Peter; Lindtner, Richard A; Langner, Cord
Abstract : This study aimed to assess the clinicopathological significance of tumour differentiation of metastatic lymph node tissue in patients with American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) stage III colorectal cancer. In a cohort of 145 patients, lymph node grades were G1 in 77 (53.1%), G2 in 41 (28.3%) and G3 in 27 (18.6%) cases, respectively. Despite differences in 77 (53.1%) cases, primary tumour and lymph node grade correlated significantly (Somer's D=0.639; p<0.001). Lymph node grade was significantly associated with N classification (p=0.009), tumour size (p=0.024) and lymphovascular invasion (p=0.004). Patients with lymph node grade G1 had better progression-free survival (p=0.031) and cancer-specific survival (p=0.008). Multivariable analysis identified lymph node grade as independent predictor of cancer-specific survival in this cohort. In conclusion, lymph node grade emerged as a promising novel prognostic variable for patients with AJCC/UICC stage III disease. Additional studies are warranted to validate this new finding.